Response of upland rice varieties to drought stress: II. Screening rice varieties by means of variable moisture regimes along a toposequence - Mambani, B.; Lal, R. (Springer, 1983)
The effects of variable soil moisture regimes along a toposequence on root development, plant water status, and grain yield were investigated for ten rice varieties: (1) 63-83, (2) IB 43, (3) OS 6, (4) IB 6, (5) IR 1529-680-3, (6) C 22, (7) IRAT-13, (8) TOS 4680, (9) IET 1444 and (10) SE 302 G. The depth of water table below the soil surface in three regions along the toposequence was 100 (M1), 30 (M2) and 15 cm (M3). Soil moisture regime did not affect total root dry weight significantly. However, depth of root penetration did vary for the different moisture regimes and varieties investigated. The angle of root penetration was also affected by soil moisture regime. Roots of tall varieties (63-83, IB 6 and IRAT 13) penetrated deeper into the soil profile than short varieties. The pattern of soil moisture depletion was similar to that of root density profile. Relative water stress, expressed as a ratio of leaf water deficit under the M1 moisture regime to that under M3, increased exponentially with decrease in root density at a depth of 25 cm. The mean grain yield was 2.4, 1.9 and 1.4 t/ha for moisture regimes M3, M2 and M1, respectively. Although the grain yield of ten varieties exhibited normal distribution under an adequate soil moisture regime (M1), the distribution pattern changed under the adverse regime. Variety IB 6 and other tall varieties maintained stable yields under the adverse moisture regime. Grain yield was linearly related to root density at a depth of 25 cm.